Intra‐arrest blood‐based biomarkers for out‐of‐hospital cardiac arrest: A scoping review - Justin L. Benoit; Andrew N. Hogan; Katherine M. Connelly; Jason T. McMullan (Journal of the American College of Emergency Physicians Open)
Abstract Objective Blood‐based biomarkers play a central role in the diagnosis and treatment of critically ill patients, yet none are routinely measured during the intra‐arrest phase of out‐of‐hospital cardiac arrest (OHCA). Our objective was to describe methodological aspects, sources of evidence, and gaps in research surrounding intra‐arrest blood‐based biomarkers for OHCA. Methods We used scoping review methodology to summarize existing literature. The protocol was designed a priori following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Extension for Scoping Reviews. Inclusion criteria were peer‐reviewed scientific studies on OHCA patients with at least one blood draw intra‐arrest. We excluded in‐hospital cardiac arrest and animal studies. There were no language, date, or study design exclusions. We conducted an electronic literature search using PubMed and Embase and hand‐searched secondary literature. Data charting/synthesis were performed in duplicate using standardized data extraction templates. Results The search strategy identified 11,834 records, with 118 studies evaluating 105 blood‐based biomarkers included. Only eight studies (7%) had complete reporting. The median number of studies per biomarker was 2 (interquartile range 1–4). Most studies were conducted in Asia (63 studies, 53%).  Only 22 studies (19%) had blood samples collected in the prehospital setting, and only six studies (5%) had samples collected by paramedics. Pediatric patients were included in only three studies (3%). Out of eight predefined biomarker categories of use, only two were routinely assessed: prognostic (97/105, 92%) and diagnostic (61/105, 58%). Conclusions Despite a large body of literature on intra‐arrest blood‐based biomarkers for OHCA, gaps in methodology and knowledge are widespread.